Characterization of Tifton 85 bermudagrass haylage with different layers of polyethylene film and storage time - Nath, Caroline Daiane; Neres, Marcela Abbado; Scheidt, Kacia Carine; Bersot, Luciano dos Santos; Monteiro Sunahara, Samantha Mariana; Wobeto Sarto, Jaqueline Rocha [UNESP]; Stangarlin, Jose Renato; Gomes, Simone Damasceno; Sereno, Mallu Jagnow; Perin, Ana Paula (Asian-australasian Assoc Animal Production Soc, 2018)
Objective: The objective was to characterize the fermentative and microbiological profile of Tifton 85 bermudagrass haylage with different layers of polyethylene film and storage time. Methods: The experimental design consisted of a randomized block design with four and six wrapping layers (100 and 150 microns in total. respectively) allocated in the main plots, through repeated measures analysis (30, 60, and 90 days of storage) with four replicates. Results: The storage time and number of wrapping layers did not show changes in the population of Clostridium and lactic acid bacteria. A decrease was observed in the enterobacteria population with an increase in the storage period in the two wrapping layers studied. Upon opening of the haylage at 30 days, the population of Bacillus was lower in haylages made with six layers of wrapping (3.63 log colony forming units/g). No growth of Listeria sp. or Salmonella sp. was observed during the experimental period. The fungal genera with a greater occurrence were Penicillium sp. and Fusarium sp. The following mycotoxins were not detected: ochratoxin A, fumonisins, and zearalenone. Relative to the organic butyric, propionic, and acetic acids, the haylages presented a low concentration of lactic acid; this may have prevented a drop in the pH, which was high when the silos were opened (5.4). The levels of ammoniacal nitrogen and soluble carbohydrates presented no variation among the number of wrapping layers, with an overall average of 35.55 and 38.04 g/kg. Conclusion: Tifton 85 bermudagrass haylage wrapped with four and six layers presented adequate fermentation and microbiological characteristics in the evaluated periods.
Keywords: Cynodon; Dehydration; Fermentation; Forage; Microorganisms